Anaemia in Diabetes Mellitus - Maimuna, Ummey (Bangladesh Journal of Medicine, 2024)
Anaemia in Diabetes Mellitus should be addressed properly. Because, anaemia in this immunocompromised state may deteriorate the physical status of this group of patients. Multiple factors have been found to be associated with anemia in Diabetes mellitus. This review article contains basic and updated concepts as well as recent studies regarding anaemia with diabetes mellitus. Bangladesh J Medicine 2024; 35: 118-121